Transmit waveform and receive filter design for multiple‐input multiple‐output radar with one‐bit digital‐to‐analogue converters - Huan Wan; Zhi Quan; Bin Liao (IET Signal Processing)
Abstract In this paper, we investigate the joint design of transmit waveform and receive filter for colocated Multiple‐Input Multiple‐Output radar equipped with one‐bit digital‐to‐analogue converters (DACs). The problem is formulated as maximising the output signal‐to‐interference‐plus‐noise ratio in the presence of signal‐dependent interferences, subject to a discrete constraint imposed by the waveform quantised with one‐bit DACs. To cope with the challenging non‐convex problem, an alternating maximisation framework is developed to optimise the transmit waveform and receive filter vectors in an iterative manner. More specifically, for a given transmit waveform vector, the analytical expression of the receive filter vector is first derived. Then, by fixing the receive filter, a biconvex relaxation method is employed to tackle the non‐convex problem with respect to the transmit waveform vector. The performance of the proposed approach is demonstrated by numerical simulations in different circumstances.